2017
DOI: 10.1002/ece3.2954
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity in female mate choice behavior is mediated by an interaction of direct and indirect genetic effects in Drosophila melanogaster

Abstract: Female mate choice is a complex decision‐making process that involves many context‐dependent factors. In Drosophila melanogaster, a model species for the study of sexual selection, indirect genetic effects (IGEs) of general social interactions can influence female mate choice behaviors, but the potential impacts of IGEs associated with mating experiences are poorly understood. Here, we examined whether the IGEs associated with a previous mating experience had an effect on subsequent female mate choice behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 88 publications
1
12
0
Order By: Relevance
“…(e.g. [21]). In this study, we showed that males who have the greatest impact on their mates' fecundity become less attractive to females after a single mating, which may explain a reduced paternity share on days 2 and 3.…”
Section: Discussionmentioning
confidence: 99%
“…(e.g. [21]). In this study, we showed that males who have the greatest impact on their mates' fecundity become less attractive to females after a single mating, which may explain a reduced paternity share on days 2 and 3.…”
Section: Discussionmentioning
confidence: 99%
“…() previously called these treatments “Monogamous (M)” and “Promiscuous (P),” we refer to them as low (L) and high (H) sexual selection treatments, as these classifications more accurately describe the conditions under which each population evolved. Promiscuity implies mating indiscriminately at random, whereas female remating patterns in D. melanogaster are known to shape by nonrandom factors (Byrne & Rice, ; Dickson, ; Dukas, ; Edward & Chapman, ; Filice & Long, ). Experimental evolution studies that manipulate mating systems (monogamy vs. polyandry/polygyny/promiscuity) do so in order to test the effects of adaptation under low and high levels of sexual selection.…”
Section: Methodsmentioning
confidence: 99%
“…2013), offer new insight into sources of variation. Indirect genetic effects (i.e., how the genotype of one individual alters the phenotype of another) can play a major role in mate choice, as they do in many other social contexts, but are just beginning to be empirically explored within the field of sexual selection (Filice and Long 2017; Trösch et al. 2017).…”
Section: Mate Choice At a Crossroadsmentioning
confidence: 99%
“…Additionally, new theoretical approaches, for example, incorporating multimodal traits (Ronald et al 2012;Wilson et al 2013) and influences of the social environment (Bailey and Moore 2012;Rodríguez et al 2013), offer new insight into sources of variation. Indirect genetic effects (i.e., how the genotype of one individual alters the phenotype of another) can play a major role in mate choice, as they do in many other social contexts, but are just beginning to be empirically explored within the field of sexual selection (Filice and Long 2017;Trösch et al 2017).…”
Section: Mate Choice At a Crossroadsmentioning
confidence: 99%